Development of a sensitive ultra high performance liquid chromatography with tandem mass spectrometry method for the simultaneous quantification of nine active compounds in rat plasma and its application to a pharmacokinetic study after administration of Viscum coloratum extracts. Issue 3 (23rd December 2014) - Fan, Rong‐Hua; Ding, Wei; Ma, Yu‐Ying; Lin, Hong‐Li; Men, Lei; Duan, Meng‐Meng; Zhao, Yun‐Li; Yu, Zhi‐Guo
<x xml:space="preserve">Abstract</x> A simple, specific, and sensitive ultra high performance liquid chromatography with tandem mass spectrometry method was developed and validated for the simultaneous quantification of nine compounds including a new compound, rhamnazin‐3‐Ο‐β‐d‐(6″‐β‐hydroxy‐β‐methyglutaryl)‐β‐d‐glucoside‐4′‐Ο‐β‐d‐glucoside, in rat plasma using baicalin as an internal standard. The plasma samples were pretreated and extracted by protein precipitation with 0.2% formic acid in acetonitrile. The analytes were separated on a Thermo Syncronis C18 column by gradient elution with a mobile phase consisting of acetonitrile and 0.1% aqueous formic acid at a flow rate of 0.25 mL/min. The detection of the analytes was performed on an electrospray ionization interface operating in positive‐ion and multiple reaction monitoring acquisition modes. The calibration curves of these analytes showed good linearity (r > 0.99) within the test ranges. The lower limit of quantification ranged from 0.4 to 20.1 ng/mL for the analytes. The intra‐ and interday precision and accuracy were all within ±15%, and the recoveries were higher than 80.0%. The validated method was successfully applied to a pharmacokinetic study of the nine flavonoids after administration of the Viscum coloratum extracts by intravenous injection.